Kepuasan Pelanggan Berbasis Kualitas Pelayanan dan Komunikasi Pemasaran - Cakrawijaya, Richard; Erdiansyah, Rezi (Kiwari, 2024)
Communication is a process of understanding and thinking that can be conveyed individually or between individuals. Marketing is an activity where a company exchanges value between itself and consumers. This research was conducted with the aim of seeing how marketing communication influences customer satisfaction at Digibank by DBS Jakarta. The author uses quantitative descriptive methods. The results of this research show that there is a positive influence between service quality in terms of customer satisfaction at Digibank by DBS Jakarta. There is a positive influence between marketing communications in terms of customer satisfaction at Digibank by DBS Jakarta. Then there is a positive influence between service quality and marketing communications in terms of customer satisfaction at Digibank by DBS Jakarta. Komunikasi merupakan sebuah proses pemahaman dan pemikiran yang dapat disampaikan individu atau antar individu. Pemasaran adalah sebuah kegiatan dimana suatu perusahaan menukarkan nilai antara mereka dengan konsumen. Penelitian ini dilakukan dengan tujuan untuk melihat bagaimana pengaruh komunikasi pemasaran dalam hal kepuasan pelanggan di Digibank by DBS Jakarta. Penulis menggunakan metode deskriptif kuantitatif. Hasil penelitian ini menunjukkan adanya pengaruh positif antara kualitas pelayanan dalam hal kepuasan nasabah di Digibank by DBS Jakarta. Adanya pengaruh positif antara komunikasi pemasaran dalam hal kepuasan nasabah di Digibank by DBS Jakarta. Kemudian terdapat pengaruh positif antara kualitas pelayanan dan komunikasi pemasaran dalam hal kepuasan nasabah di Digibank by DBS Jakarta.